Occurrence of Halogenated and Organophosphate Flame Retardants in Sediments and Eels (Anguilla anguilla) From Bizerte Lagoon, Tunisia - Mekni, Sabrine; Barhoumi, Badreddine; Touil, Soufiane; Driss, Mohamed Ridha; Eljarrat, Ethel (Frontiers in Environmental Science, 2020)
Contamination by classic (polybromodiphenyl ethers, PBDEs) and emerging halogenated flame retardants (HFRs) like pentabromobenzene (PBEB), hexabromobenzene (HBB), decabromodiphenyl ethane (DBDPE ) and halogenated norbornenes (HNs), as well as organophosphate flame retardants (OPFRs) were investigated in sediment and eel (Anguilla Anguilla) samples from Bizerte Lagoon, northern Tunisia. This is the first time that OPFR levels have been reported in this area, showing higher concentrations than HFRs: from 9.77 to 164 ng/g dry weight (dw) and from 19.7 to 2154 ng/g lipid weight (lw) for sediment and eel samples, respectively. As regards HFRs, concentrations ranged from 3.30 to 28.5 ng/g dw in sediments and from 4.72 to 151 ng/g lw in eels. The relationship between OPFR and HFR concentrations in sediment and total organic content (TOC) was examined. Results suggested that OPFR levels were significantly correlated with TOC, whereas no correlation was found for HFRs and TOC. The study of potential health risks by eel consumption suggested that there is no significant human health risk associated with the dietary intakes for PBDEs.